2017
DOI: 10.7860/jcdr/2017/20628.9449
|View full text |Cite
|
Sign up to set email alerts
|

Role of Omega-3 Fatty Acids on Lipid Profile in Diabetic Dyslipidaemia: Single Blind, Randomised Clinical Trial

Abstract: Introduction: Diabetic dyslipidaemia is characterised by hypertriglyceridaemia, low High Density Lipoprotein (HDL), postprandial lipimea, small and dense LDL particles is considered to be a major predisposing factor for various macrovascular complications. Omega-3 fatty acids are fish oil derivative introduced in the market for dyslipidaemia associated with increased triglyceride level. Aim:To study the effect of omega-3 fatty acids on lipid profile in Type II diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…Although a recent systematic review suggested that omega-3 fatty acids are not useful in the management of established cardiovascular disease, they can be an effective method of risk factor modification [17]. Specifically, omega-3 fatty acids have been shown to have a weak anti-hypertensive effect as well as an ability to reduce triglyceride levels and improve lipid profile [12,17,18]. This may, in part, explain why populations with a high dietary intake of omega-3 fatty acids have low reported levels of cardiovascular disease [19], however, the lipid lowering capacity of dietary intervention is not limited to omega-3 fatty acids.…”
Section: Nutrition In the Prevention Of Endothelial Dysfunction Anmentioning
confidence: 99%
“…Although a recent systematic review suggested that omega-3 fatty acids are not useful in the management of established cardiovascular disease, they can be an effective method of risk factor modification [17]. Specifically, omega-3 fatty acids have been shown to have a weak anti-hypertensive effect as well as an ability to reduce triglyceride levels and improve lipid profile [12,17,18]. This may, in part, explain why populations with a high dietary intake of omega-3 fatty acids have low reported levels of cardiovascular disease [19], however, the lipid lowering capacity of dietary intervention is not limited to omega-3 fatty acids.…”
Section: Nutrition In the Prevention Of Endothelial Dysfunction Anmentioning
confidence: 99%
“…It is well established that T2DM is associated with dyslipidemia ( 4) and that n-3 intake has long been indicated in the treatment of hyperlipidemia [30,31]. As cell membrane fatty acids play an important role in signal transduction, and n-3 fatty acids are capable of modifying gene expression, it is thought that the dramatic lipid-altering effects of n-3 fatty acids are mediated via this mechanism [54].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 PUFAs are reported to be associated with a range of general health benefits that include reducing the risk of cardiovascular disease, 38 39 lowering systemic triglycerides 40 and improving clinical symptoms of dry eye disease. 44 In animal models of experimental peripheral nerve injury, increasing endogenous levels of omega-3 PUFAs have been shown to improve sciatic blood flow and accelerate the recovery of neuronal function.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Increased consumption of omega-3 PUFAs is considered to provide a range of potential general health benefits, including a reduced risk of cardiovascular disease 38 39 and lowered systemic triglycerides. 40 DHA, as an integral component in cellular membrane structures of the brain and retina, has been implicated in perinatal visual and neural development. 41–43 In ocular conditions, omega-3 fatty acids supplements can reduce the symptoms and clinical signs associated with ocular surface inflammation in dry eye disease.…”
Section: Introductionmentioning
confidence: 99%